Improving Students’ Motivation in Writing Procedure Texts Through MemoryRelated Strategy - Sri Wigatiningsih (Cakrawala: Jurnal Pendidikan, 2016)
This study was to investigate the memory related strategy in relation to students’ motivation in writing procedure texts. The problemsstatement were formulated as follows: (1) what problems were faced by the students?; (2) how was Memory-related Strategy beimplemented by the students?; (3) how could Memory-related strategy improve students’ motivation in writing procedure texts? Thedesign of the research was a Classroom Action Research. The subjects of this study were the seventh grader of SMP Negeri of 1Larangan which consists of 38 students. This study was implemented in three cycles. The instruments used to collect the data wereobservation sheet, questionnaire, and students’ product. The collected data were analyzed qualitatively. The score of students’ writingimproved from pre cycle to cycle 1 to cycle 2. It can be concluded that the use of memory related strategy was able to make the studentsenjoy the writing activities.